Analysis of Sustainable Teacher Professionalism Development of Post-Certification in SD Negeri Medang Kampai District, Dumai City - Juniar, Juniar; Kartikowati, Sri; Sumarno, Sumarno (Universitas Riau, 2022)
This study aims to analyze all the aspects in implementing Teacher Professionalism Develoment (PKB) of the SD Negeri teachers in Medang Kampai, Dumai, Indonesia. The research data sources were five principals and forty-seven elementary school teachers in Medang Kampai District. The data collection technique used observation, interview and documentation techniques. The data analysis technique used the Miles and Huberman model, namely data reduction, data display, and drawing conclusions. The results showed that (1) the reasons for teachers to follow PKB were to add insight, knowledge, creativity, and improve professional competence, orders from school principals, and for promotion, (2) the efforts of teachers in implementing PKB were to follow seriously, 3) the supporting and inhibiting factors in the implementation (PKB) that come from the Office, the school and themselves, (4) the efforts of teachers in overcoming obstacles to the implementation of PKB are involving teachers in PKB activities, providing as much related information as possible, motivating teachers to continue to be enthusiastic about participating in PKB activities.